Efektivitas Cyber Law dalam Menanggulangi Pelanggaran Cybersecurity - Widurizky, Desinta; Simatupang, Elisabet; Rahmadani, Nadiyah; Auliasyah, Syifa Rahma (Journal of Informatic and Information Security, 2024)
In the growing digital era, information security information security is very crucial. This research explores the effectiveness of Cyber Law implementation in overcoming cyber security violations at Bhayangkara University, Greater Jakarta. Bhayangkara University, Greater Jakarta. By using quantitative research method quantitative research method, data was collected through distributing questionnaires to 295 respondents from informatics study program students. This research identified challenges faced, including the public's low understanding of Cyber Law and the lack of socialization in the university environment. Analysis result analysis showed that while there is an increased awareness of the importance of Cyber Law, there are still shortcomings in the application of sanctions and the protection of personal data. personal data protection. The Waterfall method was used to design a structured security system, ensuring each stage of development is optimized. This research provides recommendations to improve the understanding and application of Cyber Law to strengthen cybersecurity among university students.